The enduring value of Gánti׳s chemoton model and life criteria: Heuristic pursuit of exact theoretical biology. (21st September 2015) - Griesemer, James
Abstract: Gánti׳s chemoton model of the minimal chemical organization of living systems and life criteria for the living state and a living world are characterized. It is argued that these are better interpreted as part of a heuristic pursuit of an exact theoretical biology than as a "definition of life." Several problems with efforts to define life are discussed. Clarifying the proper use of Gánti׳s ideas to serve constructive engineering idealizations helps to show their enduring value. Highlights: Gánti׳s chemoton concept and life criteria are heuristics rather than definitions. Chemotons are autocatalytic chemical super-systems that satisfy Gánti׳s life criteria. Gánti׳s model can effectively guide theoretical and empirical research even if false.